Improvement in quality of life and cardiac function after catheter ablation for asymptomatic persistent atrial fibrillation - Naoaki Onishi; Shokan Kyo; Maki Oi; Toshikazu Jinnai; Maiko Kuroda; Yukiko Shimizu; Sari Imamura; Takeshi Harita; Suguru Nishiuchi; Koji Hanazawa; Toshihiro Tamura; Chisato Izumi; et al. (Journal of Arrhythmia, 2021)
Abstract Background Catheter ablation (CA) for atrial fibrillation (AF) is widely performed. However, the indication for CA in patients with asymptomatic persistent AF is still controversial. Methods Among 259 consecutive patients who were hospitalized for initial CA of AF, a total of 45 patients who had asymptomatic persistent AF were retrospectively analyzed. Quality of life (QOL) before and 1 year after CA was evaluated, and changes in the cardiac function over 5 years after CA were also examined. QOL was assessed using the AF QOL questionnaire (AFQLQ) developed by the Japanese Heart Rhythm Society. In addition, cardiac function was assessed by measuring the plasma B‐type natriuretic peptide (BNP) level, left ventricular ejection fraction (LVEF), left atrial diameter (LAD) with transthoracic echocardiogram, and left atrial (LA) volume with computed tomography (CT). Results The AFQLQ significantly improved after CA in terms of “symptom frequency” and “activity limits and mental anxiety.” The plasma BNP level, LVEF, and LAD significantly improved in the first 3 months after the first CA, with no significant changes thereafter (from 149.0 pg/dL [95% confidence intervals CI, 114.5‐183.5 pg/dL] to 49.8 pg/dL [95% CI, 26.5‐70.1], P < .0001; from 60.8% [95% CI, 58.1%–63.6%] to 65.0% [95% CI, 62.6‐67.4], P = .001; and from 41.3 mm [95% CI, 39.7‐42.9] to 36.8 [95% CI, 34.5‐39.1 mm], P < .0001, respectively). LA volume revealed LA reverse remodeling after CA. Conclusion Improvement in the QOL and cardiac function after CA of asymptomatic persistent AF was revealed. Asymptomatic persistent AF should be appropriately treated by CA.